GENERAL CHARACTERISTICS OF THE SYSTEM OF LEXICAL UNITS OF THE ENGLISH LANGUAGE IN THE FIELD OF LAW - Isanova Feruza Tulqinovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The present article is devoted to the study of general features of English. Language of law. Language is used in every nation to write, interpret, and uphold the law. The English language of law is acknowledged as a distinct phenomenon. Some people claim it is strange. As a result, its esoteric and enigmatic nature has often drawn criticism. This study's main goal is to improve the comprehensibility of legal English through analysis.